Influence of Early Heat Conditioning and Betaine or Ammonium Chloride Supplementation on Performance and Physiological Parameters of Quail Chicks in Hot Climate - El-Moniary, Mosaad M.; Goud, Ahmed; Hamouda, Yasser; Youssef , Amani W.; Hassan, Hussein M.A. (International Journal of Poultry Science, 2019)
Objective: This study was designed to determine the effects of early heat conditioning and betaine or ammonium chloride supplementation on growth performance and physiological parameters of quail chicks in hot climate. Materials and Methods: A total of 600-one day old quail chicks were divided into two groups, the first served as a control (non-conditioning) and the second exposed to early age heat condition (40±1ºC for 24 h at the 5th day of age). Then each group were divided into three subgroups, the first was fed the basal diet and served as a control, the second was fed the basal diet supplemented with betaine (1.5 g kg–1) and the third was fed the basal diet supplemented with ammonium chloride (0.5 g kg–1). Results: The results at 40 day of age showed that early heat conditioning with or without addition significantly (p